QQuake, a QGIS Plugin for Loading Seismological Data From Web Services - Locati, Mario; Vallone, Roberto; Ghetta, Matteo; Dawson, Nyall (Frontiers in Earth Science, 2021)
An increasing number of web services providing convenient access to seismological data have become available in recent years. A huge effort at multiple levels was required to achieve this goal and the seismological community was engaged in the standardization of both data formats and web services. Although access to seismological data is much easier than in the past, users encounter problems because of the large number of web services, and due to the complexity of the discipline-specific data encodings. In addition, instead of adopting cross-disciplinary standards such as those by the Open Geospatial Consortium (OGC), most seismological web services created their own standards, primarily those by the International Federation of Digital Seismograph Networks (FDSN). This article introduces “QQuake,” a plugin for QGIS—the Open Source Geographic Information System—that aims at making access to seismological data easier. The plugin is based on an Open Source code available on GitHub, and it is designed in a modular and customizable way, allowing users to easily include new web services.